Content Validity Assessment Using Aiken’s V: Knowledge Integration Model for Blockchain in Higher Learning Institutions - Nur Ilyana Ismarau Tajuddin; Ummu-Hani Abas; Khairi Azhar Aziz; Rozi Nor Haizan Nor; Nor Aziyatul Izni; Muhammad Nuruddin Sudin; Nur Aqilah Hazirah Mohd Anim; Noorashikin Md Noor (The Science and Information (SAI) Organization Limited, 2025)
Indexed by WOS/Scopus/ERA/MyCite